Boca de lobo, Menino oculto, El Aleph engordado y Meshugá: dinámicas del tiempo en el relato latinoamericano contemporáneo - Alves, Wanderlan (Confluenze. Rivista di Studi Iberoamericani, 2019)
In this paper we will analyse four narratives: Boca de lobo (2000) and by the Argentinean writer Sergio Chejfec, Menino oculto (2005) by the Brazilian writer Godofredo de Oliveira Neto, El Aleph engordado (2009) by the Argentinean writer Pablo Katchadjian, and Meshugá by the Brazilian writer Jacques Fux. The aim is to understand the dynamics and fragments of time which would constitute an understanding of the present time. These elements allow us to map the thematic and formal expressions of the present time in contemporary Latin American narrative.